Odevixibat treatment in a child with hypoplastic left heart syndrome and severe cholestatic pruritus: a case report - Ganschow, Rainer; Maucksch, Christof; Rauschkolb, Peter; Schneider, Martin B. E. (Frontiers in Pediatrics, 2025)
Liver-related abnormalities are commonly observed in patients with congenital heart disease, and these may lead to secondary manifestations such as pruritus. Odevixibat is an ileal bile acid transporter inhibitor under investigation for the treatment of cholestatic liver diseases. Here, we describe the effects of odevixibat treatment in a pediatric patient with congenital heart disease and severe cholestatic pruritus. A 2-year-old male with Kleefstra syndrome, hypoplastic left heart syndrome, and a history of Giessen procedure and biventricular correction surgery presented to the pediatric cardiology and hepatology outpatient clinics at University Children's Hospital Bonn. Portal hypertension was evident on imaging, and the patient was experiencing severe itching attacks that did not respond to treatment with naltrexone, ursodeoxycholic acid, dimetindene, or rifampicin. Sleep and quality of life were poor. Treatment with odevixibat was initiated off label due to refractory pruritus and elevated serum bile acids. Improvements in pruritus and sleep occurred rapidly with odevixibat and were sustained for the duration of treatment. The patient's serum bile acids decreased from 111 μmol/L before treatment with odevixibat to 24 μmol/L within 1 month of initiating therapy. Relief from pruritus had positive effects on psychomotor development and quality of life. Mild diarrhea lasting 2 days was reported by the patient's mother. In this case report, odevixibat was effective and well tolerated. Together with those of previous studies in patients with progressive familial intrahepatic cholestasis and Alagille syndrome, these results suggest that odevixibat warrants further study as a potential treatment option for patients with cholestatic pruritus of diverse etiologies.